Prevalence of Anemia and Associated Factors among Newly Diagnosed Patients with Solid Malignancy at Tikur Anbessa Specialized Hospital, Radiotherapy Center, Addis Ababa, Ethiopia - Edosa Kifle; Mintewab Hussein; Jemal Alemu; Wondemagegnhu Tigeneh (Advances in Hematology)
Background. Anemia is a common finding in cancer, which is caused by many factors. It is a major cause of morbidity in cancer patients, worsens disease status and impairs treatment outcome; however, little is known about the prevalence of anemia and associated factors among cancer patients during diagnosis in developing countries like Ethiopia. In response to this, we have conducted research with the aim of assessing the prevalence of anemia and associated factors among newly diagnosed patients with solid malignancy at Tikur Anbessa Specialized Hospital (TASH), Radiotherapy center, Addis Ababa, Ethiopia. Methods. Descriptive cross-sectional study was conducted from April to May 2014. A total of 422 newly diagnosed patients with solid malignancy attending Radiotherapy center, TASH were enrolled to assess anemia prevalence and associated factors. Data were coded, entered and analyzed using SPSS version16. Using logistic regression, chi squares, Odds ratio and 95% confidence intervals were computed to measure strength of association between variables. p-value < 0.05 was taken as statistically significant. Result. Out of 422 respondents, 285 (68%) were females and 153 (36%) of respondents fell into 35–49 age group with age range between 18 and 80 years and the median age of 45. Magnitude of solid cancers was gynecologic (28.9%), breast (22.7%), nasopharyngeal carcinoma (NPC) (7.6%), colorectal (7.1%), sarcoma (6.9%), head and neck (4.5%), thyroid (3.3%), hepatoma (1.9%), and others (17.1%). The overall prevalence of anemia across different tumor was 23% and higher anemia prevalence was noted in gynecologic (37.7%) and colorectal carcinomas (26.7%). The majority of the anemic patients (68%) remained untreated for anemia. The mean trigger hemoglobin for transfusion was 7.7 g/dl. About 83.5% of anemia was mild to moderate type. Performance status (AOR = 3.344; 95% CI 1.410–7.927) and bleeding history (AOR = 3.628; 95% CI 1.800–7.314) showed statistically significant association with occurrence of anemia with p-value < 0.05. Conclusion. Among solid cancers, gynecologic cancer remained the dominant one. Anemia prevalence was 23% in general, in which gynecologic and colorectal cancers were more prevalent. ECOG performance status and bleeding history showed a statistically significant association with the occurrence of anemia.